'FROM THE ORTHODOX MEGALOPOLIS OF MOSCOVY OF GREAT RUSSIA': RUSSIAN HEIRLOOMS FROM THE MONASTERY OF TATARNA, SIXTEENTH-SEVENTEENTH CENTURIES - Boycheva, Yuliana; Resh, Daria (Analecta Stagorum et Meteororum, 2022)
This article examines Russian artifacts donated to the Monastery of the Virgin of Tatarna (Evrytania, Central Greece) by Archbishop Arsenios of Elassona (1550-1625) and clergymen from his entourage. A monastic site since the Byzantine period, Tatarna emerged as an important religious center in the late sixteenth century because of its special status as a patriarchal monastery (stavropegion), granted to it almost immediately after its foundation by monks from Thessaly. The donation of a large number of Russian artifacts includes a manuscript, icons, and a pectoral panagiarion-encolpion, some of which are associated directly with Arsenios through inscriptions, while others are attributable to the clerics carrying the artifacts to the monastery. Overall, this is one of the very interesting ensembles of Russian ecclesiastical art to have survived in its original context in Greece. It is distinguished not only by the excellent craftsmanship of the objects comprising it, but also by the questions it raises as a historical source.